Kinerja mesin air water harvester dengan evaporator koil pada berbagai kecepatan udara masuk - Mirmanto, M.; Alit, I.B.; Maulana, A. (Universitas Mataram, 2024)
An experimental study regarding the performance of air water harvester was conducted at the natural ambient conditions. The air water harvester consisted of 3 coil evaporators and used R134a as the working fluid. The coil evaporators were constructed from copper tubes with a diameter of 6.35 mm, coil number of 26, and coil diameter of 8 cm. The air intake velocities were 4 m/s, 5 m/s, 6 m/s. The results show that the highest water mass is 1.72 kg for 7 hours at the air velocity of 6 /s, and the total heat transfer rate is 582 J/s. Increasing the air intake velocity raises the fresh water mass and the total heat transfer rate. Based on EUR the machine is not effective yet but based on the price of the water the machine gives benefit.